STUDY ON THE HABITAT PREFERENCE OF Diadema setosum IN BAMA COAST BALURAN NATIONAL PARK - Clara Puspita; Noer Moehammadi; Bambang Irawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2012)
Diadema setosum is an ecologically important sea urchin which is exists on Bama Coast, but there is no report about the presence of D. setosum in Bama Coast yet. This study was done in order to know the habitat type occurs in Bama Coast, the presence status of D. setosum, distribution pattern, the habitat preference and the character of habitat which is preferred by D. setosum in Bama Coast. Quadrate transect method was used to collect the data. Eight line transect was positioned parallel to the shore line. The transect line was 160 m in length and placed 30 m distance between transects. Quadrate plots of 1 × 1 m2 placed 4 m distance from each plotalong the transect. The habitat type was defi ned by estimated the dominant benthic cover of each plot. Measurement of physical and chemical factor of water includes sea water temperature and salinity. The Distribution pattern was determined by Poisson distribution and Chi-square simultaneously, then continued using Green coeffi cient, the habitat preference was analyzed by Chi-square and the character of habitat which is preferred by D. setosum was analyzed by selection index. The result of this study shows that there are fi ve habitat types in Bama Coast, which are sand, rubble, seagrass, live coral and dead coral. The distribution pattern of D. setosumin Bama Coast is clumped and only presence in three habitat types, which are seagrass, live coral and dead coral. Dadema setosum prefers several habitat type, which are dead coral and live coral and the character of habitat which is preferred by D. setosum is hard and solid substratum with simple architecturally structure.